Optımalısası Pembelajaran Teks Prosedur Kompleks Dalam Bahasa Indonesıa Melaluı Penerapan Project-Based Learnıng Dengan Medıa Audıovısual - Triandyah Dwi Sasi Wardani; Fida Pangesti; Sudjalil (Jurnal Elementaria Edukasia, 2023)
ABSTRACT This research is motivated by the implementation of the project-based learning model (PjBL) in the context of learning complex procedural texts at SMPN 2 Grati. This research aims to describe three main aspects, namely the application and impact of the PjBL model, the challenges faced, and students' responses to this learning model. This research used a qualitative descriptive approach with 35 class VIIA students as subjects. Data was collected through observation and interviews, documented in the form of documents and field notes. The process of data reduction, data presentation, and drawing conclusions was carried out to analyze the findings. The research results show that the PjBL model is implemented through six stages, including practicing basic questions, creating a project plan, preparing an implementation schedule, tracking student and project progress, testing results, and experience assessment. The main objective of the research reveals that the project-based learning model has a significant impact on collaboration and student learning outcomes, with the highest student average reaching 90 and the lowest 70. The proposed solution involves productive use of time, support from the homeroom teacher, and the use of informative media as an effort to overcome these difficulties. This research contributes to the practical understanding of the implementation of the PjBL model in the context of learning complex procedural texts at the secondary school level. The implications of these findings can be used as a guide for teachers and education stakeholders to increase the effectiveness and efficiency of learning in the classroom.